Insights Into the Characteristics of Sweet Syndrome in Patients With and Without Hematologic Malignancy - Zheng, Siting; Li, Sheng; Tang, Shunli; Pan, Yunlei; Ding, Yuwei; Qiao, Jianjun; Fang, Hong (Frontiers in Medicine, 2020)
Background: Sweet syndrome is a neutrophilic dermatosis that could be associated with malignancy, especially hematologic malignancy. Few studies have systematically elaborated on this disorder and its features related with hematologic malignancy. Objective: To describe the clinicopathological characteristics, treatment, and outcome of Sweet syndrome and to evaluate patient characteristics associated with hematologic malignancy. Methods: We retrospectively reviewed patients with Sweet syndrome at the Department of Dermatology, the First Affiliated Hospital of Zhejiang University from October 2010 to February 2019. Results: The study included 37 patients (16 men and 21 women), with a mean age of 53 years. Ten patients (27%) were classified as having malignancy-associated Sweet syndrome, 9 with a hematologic malignancy including acute myeloid leukemia (4/9, 44%), myelodysplastic syndrome (4/9, 44%) and multiple myeloma (1/9, 11%);one with a solid tumor diagnosed with liver cancer. The mean hemoglobin and platelet levels (P=0.007 and P=0.013, respectively) were significantly lower in patients with hematologic malignancy than in those with Sweet syndrome only. No significant difference in histopathology was found between patients with and without hematologic malignancy. Systemic corticosteroids were the most frequently used treatment (24/37, 65%). Higher mortality was found in patients with hematologic malignancy. Conclusion: It is important to assess Sweet syndrome patients who have laboratory evidence of lower hemoglobin and platelet levels for a hematologic malignancy.